Penelusuran aktivitas antibakteri, antioksidan, dan sitotoksik fungi endofit genus fusarium sp. diisolasi dari daun meniran (Phyllantus niruri Linn.) - Rollando rollando; Martanty Aditya; Dion Notario; Eva Monica; Rehmadanta Sitepu (Pharmaciana, 2017)
Endophytic fungi used as a new resource to produce bioactive compounds such as antibacterial, antioxidant and anticancer. This study aimed to analyze the antibacterial, antioxidant, cytotoxic fraction of the separation ethyl acetate extract of mycelium of endophytic fungi genus Fusarium sp. Diethyl ether fraction showed high antibacterial activity in E.coli (20,75 µg/mL), S.typhi (35,08 µg/mL), and S.aureus (51,96 µg/mL). Test showed that the antioxidant activity of ethanol 96% fraction has highest antioxidant activity and total phenolic content (75,85 ± 0.87 mg GAE). Cytotoxic test on T47D breast cancer cells showed that the fraction of diethyl ether have highest activity with IC50 of 10,16 ± 0,88 µg /mL.